The waste land and other poems - Eliot, T. S. (Thomas Stearns), 1888-1965 (Penguin classics., 2003)
"While recovering from a mental collapse in a Swiss sanitarium in 1921, T.S. Eliot finished what would become the definitive poem of the modern condition, and one that still casts a large and ominous shadow over twentieth-century poetry. Built upon the imagery of the Grail legend, the Fisher King, and ancient fertility cults, "The Waste Land" is both a poetic diagnosis of an ailing civilization and a desperate quest for spiritual renewal. Through pastiche and collage Eliot unfolds a nightmarish landscape of sexual disorder and spiritual desolation, inhabited by the voice (literary, historical, mythic, contrmporary) of an unconscious that is at turns deeply personal and culturally collective